Respuesta :
Answer:
[tex]y=\frac{1}{6}(x+1)^2[/tex] is the result of vertically shrinking
Step-by-step explanation:
Vertical stretch or shrink
[tex]y=c \cdot f(x)[/tex]
a stretch by a factor of c if c>1
a shrink by a factor of c if c<1
c is the factor
We are given that factor = 1/6 <1
So, Vertical shrink
So, [tex]y = \frac{1}{6} \cdot f(x)[/tex]
We are given that [tex]f(x) = (x + 1)^2[/tex]
So,[tex]y=\frac{1}{6}(x+1)^2[/tex]
Option D is true
Hence [tex]y=\frac{1}{6}(x+1)^2[/tex] is the result of vertically shrinking